Persepsi Ibn Sīnā dan John Locke sebagai Pengetahuan Empiris - Rizky Yazid (Refleksi, 2022)
This paper focuses on the problem of the perception of Ibn Sīnā and John Locke as an activity of knowing which is an epistemological study in philosophy. Perception therefore, is a process and a certain way to gain knowledge. The problem with this research is that as a philosopher who affirms the important role of perception, he does not necessarily become an empiricist. Or the same concern does not have direct implications for the interest of empiricism. This study uses a comparative method as its approach which aims to obtain similarities and differences regarding the concepts of the two philosophers. The findings of this study are that Ibn Sīnā has instruments for empirical research but is not an adherent of empiricism. While John Locke has the same instrument, which empirical based but as an empiricist